Exploring the Potential Link between Aluminum-Containing Deodorants/Antiperspirants and Breast Cancer: A Comprehensive Review - Hangan, Tony; Bjørklund, Geir; Chirilă, Sergiu (Current Medicinal Chemistry, 2025)
The potential association between aluminum-containing deodorants/antiperspirants and breast cancer has been investigated and debated. This paper comprehensively analyzes existing literature to examine the evidence and provide insights into this relationship. This comprehensive review discusses aspects related to the absorption and distribution of aluminum compounds, its effects on the induction of oxidative stress, the estrogenic activity of aluminum, and potential disruption of hormonal pathways, and the potential role in breast cancer induction. Currently, available research, consisting of epidemiological studies as well as clinical trials, together with meta-analyses and previously published reviews conducted on identifying the relationship between aluminum-containing deodorants/antiperspirants and the risk of breast cancer were also analyzed and discussed. Societal factors, personal hygiene considerations, and lifestyle changes contribute to the increased usage of antiperspirants, but they do not establish a direct causal connection with breast cancer. Further research employing larger-scale studies and rigorous methodologies must validate the existing findings and explore the underlying mechanisms involved. Continued multidisciplinary research efforts and collaboration between researchers, regulatory bodies, and public health authorities are vital to developing a more definitive understanding of this complex topic.
Keywords: genomic instability